Molecular geometry toolkit / Dani Asmadi Ibrahim ... [et al.] - Ibrahim, Dani Asmadi; Jamali, Amal Hayati; Md Dauad, Khairul Nizam; Mohd Yasin, Mohd Muazzin (2020)
Molecular Geometry Toolkit is a mobile education application. The toolkit allows users to make quick references, engage interactive tools and simulations related to the study of Molecular Geometry. A study involving 104 students focuses on the use of the Molecular Geometry Toolkit to help improve students’ understanding of Molecular Geometry and use it as an alternative to the traditional ball and stick model set. This study consists of two cycles. The first cycle involved the use of the application in a lecture while the second cycle involved the use of the application in a tutorial. At the end of both cycles 95% of the students scored As. Students found the application very helpful, easy to use and made the topic interesting and easier to understand. Molecular Geometry helped students learn objectives faster and at a lower cost compared to the classic ball and stick model set. This study finds the Molecular Geometry Toolkit to be a cost-effective tool for learning molecular geometry.